1986
DOI: 10.1104/pp.82.4.1145
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Enzyme Analysis of Tomato Chloroplast and Chromoplast DNA

Abstract: Plastid DNA was isolated from the chloroplasts of tomato (Lycopersicon esculentum var Traveler 76) leaves and the chromoplasts of ripe tomato fruit. Comparisons of the two DNAs were made by restriction endonuclease analysis using PvuII, HpaI, and BglI. No differences in the electrophoretic banding patterns of the restricted plastid DNAs were detected, indicating that no major rearrangements, losses, or gains of plastid DNA accompany the transition from chloroplast to chromoplast.Central to the ripening process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…2 and 3) indicated that the maize endosperm plastid genome was indistinguishable from, and likely identical to, the maize chloroplast genome. The lack of distinguishable differences at the restriction site level is consistent with studies of nongreen plastids in pepper and tomato fruit, daffodil flowers, sycamore cell cultures, and wheat endosperm (2,7,11,15,22,24 (17, unpublished data); in addition, endosperm cell division is completed and the nuclear DNA copy number increases substantially (14).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2 and 3) indicated that the maize endosperm plastid genome was indistinguishable from, and likely identical to, the maize chloroplast genome. The lack of distinguishable differences at the restriction site level is consistent with studies of nongreen plastids in pepper and tomato fruit, daffodil flowers, sycamore cell cultures, and wheat endosperm (2,7,11,15,22,24 (17, unpublished data); in addition, endosperm cell division is completed and the nuclear DNA copy number increases substantially (14).…”
Section: Discussionsupporting
confidence: 69%
“…Based on restriction endonuclease digestion patterns, amyloplasts of wheat (Triticum aestivum L.) endosperm (2) and sycamore (Acer pseudoplatanus L.) suspension cells (22), as well as the pigmented chromoplasts of tomato (Lycopersicon esculentum L.) (11,15,20), pepper (Capsicum annuum L.) fruit (7), and daffodil (Narcissus pseudonarcissus) flowers (32) contain genomes indistinguishable from the respective chloroplast genomes.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of tomato chromoplasts has been reported by others (Iwatsuki et al, 1984;Bathgate et al, 1985;Hunt et a]., 1986; Wrench et al, 1987), but we were unable to isolate pure and intact fruit chromoplasts that withstand the handling required to demonstrate successful import. However, in vitro import of an amyloplast-specific protein into chloroplasts (Klosgen et al, 1989) and the in vivo import of a chloroplast protein into nongreen plastids in transgenic plants (deBoer et al, 1988) implied that chromoplast proteins should also be imported into pea chloroplasts.…”
Section: Results and Dlscusslonmentioning
confidence: 56%
“…; is chnr~tctcrizcd by the disnppcarancc of chloroplasts (cp) and the formation of non-photosyt~tl~ctic chromoplasts (cr). CI diffcrcnriation involves a number of morphological and biochemical changes, including starch degradation, breakdown of chlorophyll and thylnkoid mcmbrancs, and synthesis and accu~~ulation of cnrotenoids 111, In addition, photosynthetic proteins and their corrcspondinp mRNAs arc absent or greatly diminished [2,3], These changes in the patterns of gene cxprcssion are not due to major recombination4 arrangements of the pt genomc, since restriction patterns of cp-and crDNAs are identical in tomato [2,4, §], and other s$ccics [6,7].…”
Section: Ntkoductionmentioning
confidence: 99%